Tick cysteine protease inhibitors suppress immune responses in mannan-induced psoriasis-like inflammation - Wu, Huimei; Jmel, Mohamed Amine; Chai, Jinwei; Tian, Maolin; Xu, Xueqing; Hui, Yuan; Nandakumar, Kutty Selva; Kotsyfakis, Michail (Frontiers in Immunology, 2024)
Protease inhibitors regulate various biological processes and prevent host tissue/organ damage. Specific inhibition/regulation of proteases is clinically valuable for treating several diseases. Psoriasis affects the skin in the limbs and scalp of the body, and the contribution of cysteine and serine proteases to the development of skin inflammation is well documented. Cysteine protease inhibitors from ticks have high specificity, selectivity, and affinity to their target proteases and are efficient immunomodulators. However, their potential therapeutic effect on psoriasis pathogenesis remains to be determined. Therefore, we tested four tick cystatins (Sialostatin L, Sialostatin L2, Iristatin, and Mialostatin) in the recently developed, innate immunity-dependent mannan-induced psoriasis model. We explored the effects of protease inhibitors on clinical symptoms and histological features. In addition, the number and percentage of immune cells (dendritic cells, neutrophils, macrophages, and γδT cells) by flow cytometry immunofluorescence/immunohistochemistry and, the expression of proinflammatory cytokines (TNF-a, IL-6, IL-22, IL-23, and IL-17 family) by qPCR were analyzed using skin, spleen, and lymph node samples. Tick protease inhibitors have significantly decreased psoriasis symptoms and disease manifestations but had differential effects on inflammatory responses and immune cell populations, suggesting different modes of action of these inhibitors on psoriasis-like inflammation. Thus, our study demonstrates, for the first time, the usefulness of tick-derived protease inhibitors for treating skin inflammation in patients.